2022
DOI: 10.3390/app12020840
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Quantification of Chlorophylls, Carotenoids, Phenolic Compounds, and Vitamins from Halophyte Biomasses

Abstract: Halophytes are salt-tolerant plants, and they have been utilised as healthy, nutritious vegetables and medicinal herbs. Various studies have shown halophytes to be rich in health-beneficial compounds with antioxidant activity, anti-inflammatory and antimicrobial effects, and cytotoxic properties. Despite their potential, these plants are still underutilised in agriculture and industrial applications. This review includes the state-of-the-art literature concerning the contents of proanthocyanidins (also known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 99 publications
5
15
1
Order By: Relevance
“…The concentration of total carotenoids in Salicornia spp. varies between different studies [ 16 ], and all obtained results lay within the range of reported results. Carotenoids are non-enzymatic antioxidants produced in response to different stressors [ 67 ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The concentration of total carotenoids in Salicornia spp. varies between different studies [ 16 ], and all obtained results lay within the range of reported results. Carotenoids are non-enzymatic antioxidants produced in response to different stressors [ 67 ].…”
Section: Resultssupporting
confidence: 84%
“…Due to adaptation to extreme environmental conditions and a high natural defence against predators and pests, Salicornia spp. produce high concentrations of bioactive secondary metabolites, such as phenolic acids, flavanols, flavones, and flavanones [ 3 , 15 , 16 ]. These metabolites have reported health-beneficial properties, including antioxidant, anti-inflammatory, and anti-diabetic activities [ 7 , 15 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To adapt to harsh environmental conditions, particularly high levels of salinity and UV exposure, halophytes produce signi cant amounts of bioactive secondary metabolites such as phenolic acids, avonoids, and tannins [18,50,51]. These compounds exhibit a wide range of health bene ts, including antioxidant, anti-in ammatory, anti-cancer, and anti-diabetic activities [50,[52][53][54][55].…”
Section: Chemical Pro Lementioning
confidence: 99%
“…High-value bioactive compounds suitable for cosmetics and pharmaceutical ingredients can also be found from Salicornia spp. 27 , 29 32 , Tripolium pannonicum 33 , 34 and Crithmum maritimum 35 , 36 extracts, and these compounds have exhibited antioxidant activity, anti-inflammatory and antimicrobial effects, anti-obesity properties, and even cancer-preventing capabilities.…”
Section: Introductionmentioning
confidence: 99%